Repositórios digitais confiáveis: as transferências e a verificação de compatibilidade entre modelos internacionais de critérios de preservação digital no longo prazo e o RDC-Arq - Fábio Lopes de Andrade (2021)
This work aimed to analyze the criteria of the Catalogue of Criteria for Trusted Digital Repositories (NESTOR) of the Trustworthy Repositories Audit & Certification: Criteria and Checklist (TRAC) and the Audit and Certification of Trustworthy Digital Repositories (ACTDR). The criteria were compared with the requirements of the Guidelines for the Implementation of Reliable Digital Repositories (RDC-Arq), observing the similarities and differences regarding the agents of the preservation actions, the preservation actions, and the digital objects targeted by these preservation actions, listed in each requirement; as well as auditing and certification actions in each of the digital preservation models. The objective was to elaborate a hybrid conceptual model, fruit of the analysis of the three requirement models mentioned above, and propose a form for self-evaluation of reliable digital archival repositories, adapted to the Brazilian context, that can subsidize future RDC-Arq updates. At the same time, we investigated how to proceed with the transmission of Information Submission Packages to the RDC-Arq, observing Decree nº 10,278/2020 and international experiences of archival and digital preservation institutions for long periods, to propose appropriate technical procedures for digital archival preservation in the Brazilian context. The purpose was to develop procedures allied to open source software technologies distributed free of charge to provide Producers and archives of institutions reached by Decree 10,278/2020 with appropriate tools to maintain the legal value of digitized archival documents. The methodology used was the bibliographic review in scientific research aimed at long-term digital preservation, notably those cited in the RDC-Arq. We compared quantitatively and qualitatively the requirements and criteria of models aimed at auditing and certifying digital repositories in search of similarities and conceptual differences. In conclusion, TRAC shows a high conceptual similarity to the RDC-Arq and already has software available to assist the audit work. The NESTOR Catalog presented significant conceptual amplitude criteria but high non-similarity to the RDC-Arq. The ACTDR proved to be more complex and detailed than the RDC-Arq, and it is possible to see a relatively conceptual similarity between them. Decree 10.278/2020 left many gaps in technical and methodological specificities for the proper transmission of Information Submission Packages between Producers and institutions covered it. Finally, we suggest a proposal of action flow combined with appropriate software to maintain integrity, validation, and search for malicious codes, making the transmission of digital archival objects viable and secure.